2019
DOI: 10.1186/s40359-019-0286-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between the big five personality characteristics and dietary habits among students in a Ghanaian University

Abstract: Background Adherence to good dietary practices has been linked to disease prevention and better quality of life yet, University students are known to have poor dietary intake and diet quality. For an effective behaviour modification in dietary habits, an understanding of the association between an individual’s personality traits and dietary habits are of much significance. The aim of this study was to determine the relationship between personality traits and dietary habits among Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 29 publications
3
33
0
1
Order By: Relevance
“…Such a configuration of personality traits may be associated with the field of study, because physical activity may realize the high demand for stimulation (with high extraversion) and improve emotional state. The relatively high level of openness and conscientiousness of the surveyed physical education students corresponds to the results of research obtained for students of various university faculties from Ghana [ 16 ].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Such a configuration of personality traits may be associated with the field of study, because physical activity may realize the high demand for stimulation (with high extraversion) and improve emotional state. The relatively high level of openness and conscientiousness of the surveyed physical education students corresponds to the results of research obtained for students of various university faculties from Ghana [ 16 ].…”
Section: Discussionsupporting
confidence: 66%
“…The complex interaction between psychological, cultural, environmental, and behavioral factors may influence the modification of an individual’s eating habits. Earlier studies in the field of personality determinants of nutritional behaviors in academic youth concerned, for example, food choices among students of Polish (Kraków) universities [ 14 , 15 ], eating habits among students of various faculties in Ghana [ 16 ], eating disorders in Korean medical students [ 17 ] and in Lebanese students [ 18 ], eating disorders and alcohol consumption among American students [ 19 ], and the intake of dietary supplements by Japanese students [ 20 ]. On the other hand, comparative research in the field of geographical and cultural determinants regarding the nutritional behavior of academic youth concerned, among others, students from Spain (Murcia) and Poland (Gdańsk) [ 21 ], Spain and Romania [ 6 ], and from four other European countries (Poland, Bulgaria, Denmark, and Germany) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That meal skipping for weight management was associated with all three personality traits-higher neuroticism and extraversion, F I G U R E 1 Multiple mediation model for oral health regressed on conscientiousness through diet variables (standardized coefficients reported; household income, socioeconomic position, and indigenous status held constant in model; computed using 10,000 bootstrap resamples) and lower conscientiousness-is an important new finding. A previous study explored these associations in a small sample of adults and found that these personality traits were unrelated to meal skipping (Intiful et al, 2019). In addition to measures at age 12, increases in neuroticism and decreases in conscientiousness between ages 12 and 14 were also associated with a greater occurrence of meal skipping for weight management.…”
Section: Discussionmentioning
confidence: 96%
“…There is also some emerging evidence that higher levels of extraversion (Keller & Siegrist, 2015) and neuroticism (Tiainen et al, 2013) relate to a greater consumption of high sugar drinks. One study also explored meal skipping behavior in Ghanaian university students and found that personality traits were generally unrelated to meal skipping (Intiful, Oddam, Kretchy, & Quampah, 2019).…”
mentioning
confidence: 99%